Risk perception, well-being, depression and anxiety in children and adolescents with rheumatic diseases during the COVID-19 pandemic - results from the prospective multicenter KICK-COVID study in Germany - Claudia Sengler; Jens Klotsche; Malthe Jessen Pedersen; Martina Niewerth; Julia Göldel; Daniel Windschall; Johannes-Peter Haas; Frank Dressler; Ralf Trauzeddel; Anton Hospach; Frank Weller-Heinemann; Stefanie Lanzinger; et al. (BMC, 2024)
Abstract Objective To investigate the psychosocial burden in children and adolescents with juvenile rheumatic diseases during the COVID-19 pandemic. Methods As part of the multicentre observational KICK-COVID study linked to the National Pediatric Rheumatology Database, adolescents < 21 years and parents of children < 12 years with rheumatic diseases answered questions on perceptions of health risk (PHR) due to SARS-CoV2, stress, well-being (WHO-5) and symptoms of depression (PHQ-9) and anxiety (GAD-7). Data were collected at routine visits from June to December 2021 and assessed for association with demographic and clinical parameters, treatment and patient-reported outcomes by multivariable regression analyses. Results Data from 1356 individuals (69% female, 50% adolescents) were included. Median PHR on a numeric rating scale (NRS, 0-10) was 4 (IQR 2-6), median perceived stress was 3 (IQR 1-6). Adolescents reported a worse well-being with a significantly lower median WHO-5-score (60, IQR 40-76) than parents reported for their children < 12 years (80, IQR 68-84). Moderate to severe symptoms of depression and anxiety were reported by 14.3% and 12.3% of the adolescents, respectively. PHR was significantly higher in patients with systemic lupus erythematosus, methotrexate or biologic disease-modifying anti-rheumatic drug therapy than in patients without these characteristics, whereas lower WHO-5 or higher PHQ-9 or GAD-7 scores were only associated with poorer patient-reported health status and physical functioning. Conclusion The perception of health risk due to SARS-CoV2 infection was not paralleled by an impairment of mental health, which were, however, significantly correlated with self-rated health status and functional capacity, highlighting the importance of patient-reported outcome assessment. Trial registration German Clinical Trials Register (DRKS), no. DRKS00027974. Registered on 27th of January 2022.